STRATEGI KEPALA SEKOLAH DALAM UPAYA PENGUATAN BUDAYA MUTU DI LEMBAGA PENDIDIKAN ISLAM: indonesia - Damayanti, Baktina; Nur Indah Hidayati; Saipul Annur; Asri Karolina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: (1) describe the principal's strategies in building quality culture at Sekolah Qur'anpreneur Indonesia (SQI) Palembang; (2) analyze the implementation of quality culture strengthening strategies; and (3) identify supporting and inhibiting factors in quality culture reinforcement. The study employed a qualitative case study design. Data were gathered through in-depth interviews, participatory observation, and documentation from thirteen purposively selected informants. Data analysis followed the interactive model by Miles, Huberman, and Saldaña, with validity ensured through source and method triangulation. Findings reveal that the SQI principal applies three core strategies: internalizing Islamic values (itqan, amanah, istiqamah) as measurable performance standards; empowering an Islamically-grounded professional learning community; and strengthening data-based accountability systems. Implementation follows a continuous improvement cycle adapted from the PDCA model. Key supporting factors include leadership commitment and foundation support, while high teacher turnover and resistance to digitalization constitute the main inhibiting factors. These findings contribute to the development of a value-based leadership model for Islamic educational institutions.